SMOKING BEHAVIOUR AMONG MIDDLE AND LATE ADOLESCENTS IN A SUB DISTRICT OF MALANG DISTRICT, EAST JAVA, INDONESIA - Yuyud Wahyudi; Peerapong Boonsawasdgulchai (UNEJ e-Proceeding)
As one of countries with high cigarettesconsumptions in the world (Eriksen et al., 2012;Lian and Dorothea, 2014), many people inIndonesia have suffered from various diseasescaused by smoking behavior (Lian & Dorothea,2014; WHO, 2012). However, the prevalence ofsmoking among people 15 years old and abovewere remains high (34.8%) (WHO, 2012).Many Indonesian adolescents had difficulties tofind facilities which could help them to quitsmoking (Aditama et al., 2008). Thus, who werewilling to quit smoking common use self helpmethods (Ng et al., 2007). The appropriate strategyon smoking cessation program was very importantto prevent smoker adolescents entered intonicotine dependencies (Karpinsky et al., 2010)Malang District was a district which was includedinto top ten Districts in Indonesia which had highproportions of daily smoker age 10 years old andabove (27.6 %) (Balitbangkes, 2008). Lackimplementation of the government regulationmight have correlation with high percentage ofsmoker among youth within Malang District.(Health Department of Malang District, 2015). Thisstudy aims to explore smoking behavior and thetriggers of smoking between middle and lateadolescents in a Sub – District of Malang District,East Java - Indonesia.